Vulnerability of elasmobranchs caught as bycatch in the grouper longline fishery in the Gulf of Gabès, Tunisia - SAIDI , BECHIR; ENAJJAR, SAMIRA; BRADAI, MOHAMED NEJMEDDINE (Mediterranean Marine Science, 2023)
The present study aims to quantify the effect of the grouper demersal longline fishery to elasmobranchs in the Gulf of Gabès to support future conservation actions for the most vulnerable species. Data from 162 demersal longline sets carried out during the grouper fishing seasons in 2016 and 2017 were analyzed. At least 17 elasmobranch species were caught, representing about 50% of the total catch in number which exceeded the target catch of groupers Epinephelus spp. (44.15%). Elasmobranchs were present in 139 (85.80%) out of the 162 examined sets, while the frequency of occurrence per set varied greatly depending on the species. The nominal Catches Per Unit Effort of all species combined was 3.07 specimens per 1,000 hooks/hour of fishing. Sharks and batoids contributed equally to the total elasmobranch catch, comprising 51.84% and 48.16% in terms of number, respectively. Mustelus mustelus, Carcharhinus plumbeus and Squalus spp. were the most abundant species, representing 45.65% of the total elasmobranch catch, whereas the remaining shark species were rarely caught (6.19%). Batoids were dominated by Glaucostegus cemiculus, which represented 19.07% of the total elasmobranch catch in number, followed by Dasyatis spp. (8.91%), Raja clavata (7.1%) and Taeniura grabata (4.59%). The elasmobranchs discarded due to their low commercial value and/or small size represented 11.34% of the total catch in number. According to the results of the Productivity and Susceptibility Analysis, the coastal viviparous elasmobranch species in the study area are highly vulnerable to the grouper longline fishery activity and should be carefully managed to reduce the likelihood of overfishing.